Coprecipitation technique to prepare NaNbO3 and NaTaO3 - Samuel, V; Gaikwad, A. B.; Ravi, V (Bulletin of Materials Science, 2006)
A simple coprecipitation technique has been used successfully for the preparation of pure, ultrafine, single phases of NaNbO3 (NN) and NaTaO3 (NT). An alcoholic solution of ammonium carbonate and ammonium hydroxide was used to precipitate Na+ and Nb5+ (or Ta5+) cations under basic conditions as carbonate and hydroxide, respectively. On heating at 700 degrees C, these precursors produce respective products. For comparison, both NN and NT powders were also prepared by the traditional solid state method. The phase purity and lattice parameters were studied by powder X-ray diffraction (XRD). The particle size and morphology were studied by scanning electron microscopy (SEM).
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods